Islamic Donations-based Crowdfunding Platforms in Malaysia: An Evaluation of Regulatory and Shariah Issues - Rafisah Mat Radzi; Nurul Aini Muhamed; Muhammad Iqmal Hisham Kamaruddin; Wan Nur Fazni Wan Mohamad Nazarie; Aimi Fadzirul Kamarubahrin (Lembaga Kajian Konstitusi Indonesia (LKKI), Fakultas Syariah dan Hukum, Universitas Islam Negeri Ar-Raniry, 2024)
PETITA: Jurnal Kajian Ilmu Hukum Dan Syariah (PJKIHdS) Volume: 9 No:2 (page: 413–434)